2023
DOI: 10.1007/s11136-023-03341-0
|View full text |Cite
|
Sign up to set email alerts
|

Disagreement between mothers' and fathers' rating of health-related quality of life in children with cancer

Abstract: Purpose Serial assessment of health condition based on self-report made by children and their proxies has consistently shown a lack of congruence. The study explored the discrepancies between mother’s, father’s, and children’s reports on health-related quality of life (HRQOL) during the first two months of pediatric cancer treatment. Methods In this cohort study, children and parents completed the generic and cancer-specific Pediatric Quality-of-Life Inven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…36,37 Also in the highincome context, Meryk et al showed that fathers' estimates of quality of life and physical functioning were more discrepant from self-reports than mothers' accounts. 38 Therefore, concepts included in the questionnaire may have been less culturally accepted, new or misunderstood by especially the fathers.…”
Section: Discussionmentioning
confidence: 99%
“…36,37 Also in the highincome context, Meryk et al showed that fathers' estimates of quality of life and physical functioning were more discrepant from self-reports than mothers' accounts. 38 Therefore, concepts included in the questionnaire may have been less culturally accepted, new or misunderstood by especially the fathers.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in this study, a lower agreement was observed for the overall HRQoL across both the measures for children without any reported health condition than those with reported health conditions. Additionally, a higher maternal than paternal involvement in childcare has been linked to the higher mother–child agreement levels evident in literature [ 17 , 55 , 56 ]. In this study, a similar trend was observed with the CHU9D, but this was not consistently reflected with the PedsQL TM .…”
Section: Discussionmentioning
confidence: 99%